Endoscopic submucosal dissection for early squamous cell carcinoma in the anal canal and Lugol chromoendoscopy for assessment of the lateral margin - Uozumi, Takeshi; Sumiyoshi, Tetsuya; Kondo, Hitoshi; Minagawa, Takeyoshi; Fujii, Ryoji; Yosida, Masahiro; Tokuchi, Kaho; Mizukami, Takuya; Morita, Koutarou; Ihara, Hideyuki; Okagawa, Yutaka; Takayama, Toshizo; Ooiwa, Shutaro; Hirayama, Michiaki; Oyamada, Yumiko (Endoscopy International Open, 2018)
A 66-year-old man underwent follow-up colonoscopy after colon polypectomy. The retroflexed view of the anal canal with white-light imaging revealed a whitish, slightly elevated lesion on the dentate line and an ill-defined flat lesion. A biopsy of the whitish elevation revealed squamous cell carcinoma (SCC), and endoscopic submucosal dissection (ESD) was planned. The lateral margin of the SCC was identified by spraying with Lugol’s iodine, and the tumor was resected en bloc with no complications. The pathological findings were SCC in situ with parakeratosis in the whitish elevation and high-grade intraepithelial neoplasia in the ill-defined flat lesion, which exhibited a wide iodine-unstained area by chromoendoscopy. Early SCC in the anal canal is a rare gastrointestinal cancer, and Lugol chromoendoscopy helped visualize the tumor margin for ESD.